The potential of leveraging electrostatics for improved inhaled drug delivery to the lungs - Bessler, Ron; Sznitman, Josué (Frontiers in Medical Engineering, 2024)
In this short perspective, we explore the potential of leveraging electrostatic forces in the lungs to enhance pulmonary drug delivery methods and optimize drug delivery efficiency and therapeutic outcomes. Alongside conventional mechanisms such as diffusion, gravitational sedimentation, and impaction, we delve into electrostatic mechanisms, utilizing a non-dimensional analysis approach for insights into aerosol drug delivery. While often overlooked in inhalation therapy, our considerations emphasize the significance of electrostatic interactions on drug deposition, particularly in the deep lung, where, in the future, tailored electrostatic charges can strategically offer new possibilities for localized therapeutic effects for respiratory diseases.